2023
DOI: 10.1186/s43014-022-00121-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic-protein interactions: insight from in-silico analyses – a review

Abstract: Phenolic compounds are ubiquitous plant secondary metabolites that possess various biological activities and are known to interact with proteins, altering their structure and properties. Therefore, interactions between these compounds and proteins has gained increasing attention due to their potential benefits to human health and for exploitation by the food industry. Phenolic compounds and proteins can form complexes via covalent linkages and/or non-covalent interactions through hydrophobic, electrostatic, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 101 publications
0
22
0
Order By: Relevance
“…It has been reported that, on the one hand, the action of biochemical factors can facilitate compound release from the physical food matrix structure and complexes with its macromolecular components; on the other hand, complexation with digestion enzymes may decrease the content of free compounds [ 25 , 31 , 32 ]. Presumably, the limited effect of biochemical factors on bioaccessibility found in this study was connected with the specific character of the applied phytochemicals subjected to digestion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, on the one hand, the action of biochemical factors can facilitate compound release from the physical food matrix structure and complexes with its macromolecular components; on the other hand, complexation with digestion enzymes may decrease the content of free compounds [ 25 , 31 , 32 ]. Presumably, the limited effect of biochemical factors on bioaccessibility found in this study was connected with the specific character of the applied phytochemicals subjected to digestion.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of phenolic acid compounds on protein rigidity provide a deeper understanding of the inhibitory mechanism at the structural level. Stabilization of the protein–ligand complex and subsequent decrease in protein rigidity provide compelling evidence for the disruption of the normal function of the enzyme by phenolic acid compounds . TNF-α convertase inhibition has emerged as a potential strategy for anti-inflammation due to its crucial role in regulating inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists have achieved much progress in strengthening and clarifying the formation of polyphenol-protein covalent complexes through prevalent utilization of molecular docking for predicting phenolic compounds and protein binding sites ( 136 ). However, limited research has been conducted on comprehensively determining the binding sites and identifying the specific amino acid residues that directly contribute to the formation of polyphenol-protein covalent complexes.…”
Section: Summary and Future Perspectivementioning
confidence: 99%